A review on recent status and challenges of yttria stabilized zirconia modification to lowering the temperature of solid oxide fuel cells operation - Zakaria Z.; Abu Hassan S.H.; Shaari N.; Yahaya A.Z.; Boon Kar Y. (John Wiley and Sons Ltd, 2023)
Cost reduction; Durability; Ionic conductivity; Solid oxide fuel cells (SOFC); Temperature; Yttria stabilized zirconia; Yttrium oxide; Zirconia; Electrochemical energy converters; Intermediate temperatures; Mechanical and thermal properties; Oxide-ion conductivity; Portable applications; Power generation systems; Solid oxide fuel cells (SOFCs); Yttria-stabilized zirconias (YSZ); Solid electrolytes